Effect of Semi-Rigid Connection on Post-Buckling Behaviour of Frames Using Finite Element Method - Douaa Raheem Mohammed; Murtada A. Ismael (Civil Engineering Journal, 2019)
It is very important task to estimate the post buckling for structures that have slender elements, since post-buckling state means loss the structures stability related with large displacement and that lead to demolition the structures. On the other hand, in the design and analysis of steel frame, the beam-columns connection is assumed perfect pin or fully rigid, this assumption leads to incorrect estimation of the structural behaviour. Practically, beam-column connection is between these two assumptions and this type of connection is called semi-rigid. This study presents a numerical analysis using finite element method to investigate the effect of semi-rigid connections on post-buckling behaviour of two-dimensional frames with different supporting types and different lateral loading cases. The semi-rigid connections are modelled as rotational spring in linear elastic stage, using COMBIN14 element which has rotational stiffness value.  The numerical results showed that; the effect of changing the beam-column connections from rigid to semi rigid for toggle frame with rotational joint stiffness 25EI/L to 15EI/L and 10EI/L led to decrease the initial peak load of the frames of fixed-fixed supports with percentages 3.36 %, 5.6% and 8.95% respectively as compared with that of the rigid connection frame, While, the frames with fixed-pin and pin-pin supports cases did not affected by this changing. The fixed-fixed support case is more affected by changing the joint stiffness from other cases and the effect of changing the joint stiffness in pin-pin support model is less significant from others. This can be attributed to that, the fixed-fixed supports is restrained in all degree of freedom and will be affected by any rotation and presence the pin in other cases makes the frame less affected by the rotation of semi-rigid connection. The effect of changing the beam-column connection from rigid to semi rigid decreases with presence the lateral load. Thus, the semi-rigid connection should be considered in analysis and design of steel frames to obtain more realistic results.